Enhancing Language Learning Through Ethnopedagogical Blended STEM: Effects on Students’ Creative and Problem-Solving Competencies - Everhard Markiano Solissa; Sukini Sukini; Burhan Efendi; Tomi Apra Santosa; Hasyim Mahmud Wantu; Unpris Yastanti (Universitas Pendidikan Mandalika, 2025)
This study aims to investigate the effectiveness of ethnopedagogical mixed STEM approaches in improving students' creative thinking and problem-solving skills in the context of language learning. Using 24 empirical studies published between 2020 and 2024, the study synthesized quantitative findings to determine the overall effect size and identify moderator variables that could influence learning outcomes. The data encoding follows PRISMA guidelines, and statistical analysis is performed using JASP software. The analysis yielded a significant overall effect measure (Hedges' g = 0.78, p <0.001), which demonstrated a strong positive impact of ethnopedagogically blended STEM learning on creative skills and problem-solving in language education. The moderator analysis showed that education level and duration of learning significantly moderated the effect size, while the year of publication and geographic region did not show significant moderation. These findings support the integration of culturally responsive STEM-based pedagogy in language teaching and highlight the importance of contextual-based learning models for fostering 21st-century skills.